Urgensi Pengaturan Bea Masuk Anti-Dumping : Produk Ubin Keramik Impor China di Indonesia - Faiz Ghozi Al Kamil (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article aims to discuss the urgency of regulation related to anti-dumping import duties on Chinese imported products in Indonesia resulting in losses for the domestic ceramic industry due to dumping actions carried out by Chinese ceramic importers to Indonesia. Regarding the actions taken by China, including dumping, it can be subject to anti-dumping import duties as stipulated in Law Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning Customs, Government Regulation Number 34 of 2011 concerning Anti-Dumping, Reward Measures, and Trade Security Measures, and Law Number 7 of 2014 concerning Trade. The rules listed are an effort to stop losses for the domestic ceramic industry and new legal products must be immediately presented in the Ministerial Regulation, especially the Minister of Finance and the Minister of Trade so that there is legal certainty.